Biphasic synovial sarcoma: A rare cause of axillary mass - Demirli Atıcı, Semra; Yeşilyurt, Değercan; Dikmeer, Emre; Salimoğlu, Semra; Ayaz, Duygu; Aydın, Cengiz (Journal of Surgery and Medicine, 2019)
Synovial sarcoma is a subtype of soft tissue sarcoma which mostly affects the lower extremities, especially in young adults. Axillary involvement of the synovial sarcoma is a rarely seen clinical condition. A 68-year-old female applied with a rapidly grown palpable 4x4cm conglomerated mass in her right axilla. Except for the palpable axillary mass, her physical examination was regular. She was scanned for any distant metastasis with thoracoabdominal computerized tomography and breast ultrasonography with mammography. Tru-cut biopsy was performed on the palpable conglomerated axillary mass, and the pathological examination of the tru-cut biopsy specimen was reported as biphasic malignancy. In order to obtain a detailed examination and definite diagnosis, the mass was dissected and resected from axilla with extensive resection. Postoperative pathological examination was reported as a biphasic SS, and the surgical margins were clear. During the post-operative period, the patient had adjuvant chemoradiotherapy. There was no tumor relapse, both clinically and radiologically fourteen months after the surgery. Elder patients presenting with axillary lymphadenopathy, atypical, rare synovial sarcoma should be kept in mind. Total surgical excision should be performed, and clear margins should be obtained for the treatment of localized synovial sarcoma of the axilla.